The Awareness of the Indonesian Market Toward the Corporate Social Responsibility of a Company - Rintan Nuzul Ainy; Alia Ariesanti (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2022)
The existence of CSR institutions and associations coherent with several laws and regulations concerning CSR applied in Indonesia indicates that Indonesia gives more attention to the importance of CSR. The increasing number of parties who appreciate CSR performance also motivates companies to commit to implementing CSR. However, the next question is related to whether the public (market) responds to the efforts of the government, companies, and all parties involved in the progress of CSR in Indonesia or not. Specifically, the question lingers around whether the Indonesian market is aware of the importance of CSR or not. Departing from the two questions, the study aims to determine the response of the Indonesian market after the CSR-related information has been identified since market responses will show awareness of the importance of CSR. The data that have been used in the study are the secondary ones and include the stock prices that come from 5 days before and 5 days after the announcement of the Indonesia Sustainability Reporting Award (ISRA) 2017 and 2018. The hypothesis test results show no differences in stock prices between 5 days before and 5 days after the announcement of the ISRA award. On the contrary, the hypothesis test results show that the Indonesian market has not responded to CSR information of a company. The reason is that the Indonesian market does not consider CSR information relevant for investment decision making.